Instagram Religious Moderation Dialogue Space for Generation Z - rama kertamukti (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
Lifestyle by using social media and as followers of religion make Generation Z Indonesia must be able to respond to differences. The reality that occurs in Indonesia is Instagram social media is very popular and in accordance with their lifestyle. The Instagram space in its activities facilitates the application of wisdom values to accept differences that lead to religious moderation for Generation Z. provide religious moderation. Their account builds tolerance by actively, and provides wisdom values in its content. This researchusing a qualitative study with a virtual ethnographic study. The subject in this study is an Instagram account with the characteristics of having religious moderation content that has a positive impact on followers. Selection of methodology Virtual ethnography can see the way of life of Generation Z in their daily activities using or following social media accounts. The results in this study are social media accounts as the subject of this study provide a strong message strategy for Generation Z. The messages in these accounts are favored by Generation Z in understanding religious moderation because the messages generated pay attention to; messages that are humane and have a positive and good perception can be seen from the comments of the followers. The message that was built made Generation Z more sensitive from the start to understand differences (being moderate, open and tolerant in the midst of differences). The stages in building messages carried out by these accounts are: the stages of creating messages, evaluating messages, selecting.Keywords: Virtual ethnography, Instagram, Generation Z, religious moderation ABSTRAKGaya hidup dengan menggunakan media social dan sebagai pemeluk agama menjadikan Generasi Z Indonesia harus dapat menyikapi perbedaan. Kenyataan yang terjadi di Indonesia media social Instagram sangat disukai dan sesuai dengan gaya hidup mereka. Ruang Instagram dalam aktivitasnya memudahkan penerapan nilai-nilai kearifan untuk menerima perbedaan yang mengarah pada moderasi beragama bagi Generasi Z. Akun @milenialislami.id, @friends_islami, @husein_hadar, ideclare_id, @ yerry_pattinasarany dalam praktik di dalam akun mereka, menjalin diskusi dan aktivitas dalam memberikan moderasi beragama. Akun mereka membangun toleransi dengan aktif,dan memberikan nilai-nilai kearifan didalam kontennya. Penelitian ini menggunakan studi kualitatif dengan studi etnografi virtual. Subjek dalam penelitian ini adalah akun Instagram dengan karakteristik memiliki konten moderasi beragama dampak positif bagi pengikutnya. Pemilihan metodologi Etnografi virtual dapat melihat cara hidup generasi Z dalam beraktivitas keseharian menggunakan atau mengikuti akun-akun media sosial. Hasil dalam penelitian ini adalah akun media sosial sebagai subjek penelitian ini memberikan strategi pesan yang kuatbagi Generasi Z. Pesan-pesan dalam akun tersebut disukai generasi Z dalam memahami moderasi beragama karena pesan yang dihasilkan memperhatikan; pesan yang humanis dan memiliki persepsi yang positif dan baik terlihat dari komentar para follower. Pesan yang dibangun menjadikan generasi Z lebih peka sejak awal mengerti tentang perbedaan (bersikap moderat, terbuka dan toleran ditengah perbedaan). Tahapan dalam membangun pesan yang dilakukan akun-akun tersebut adalah yaitu: tahapan mengkreasi pesan, mengevaluasi pesan, memilih, dan mengimplementasikan pesan dengan detail terlihat dalam jumlah follower yang meningkat.Kata Kunci: Etnografi virtual, Instagram, Generasi Z, moderasi beragama